Enhancing Students' Learning Performance in Physical Education Through the Use of a Mobile Application with Game-Based Learning Approach - Carla Jobelle Culajara (Physical Education and Sports: Studies and Research, 2023)
Background: In response to the transition of learning from confinement at home and now having in-person classes, being flexible to the needs of students must be innovative and creative to slowly get their attention and motivation to learn. Objectives: The objective of the study is to determine the effect of the developed mobile application to students learning performance in Physical Education. Methods: The researcher used quasi-experimental research design utilizing pretest and posttest. Purposive sampling was used to determine the participants consisting of 25 students under control group and 25 students under experimental group which were Grade 10 students in one of the secondary schools in the Philippines. JASP Software was used to analyze the data used in the study. The research instrument was validated by the Head Teacher and Master Teacher. Results: Data revealed that the developed mobile application has a tremendous effect on students learning performance in Physical Education. It shows that the mean scores in the before utilization on the group using the developed mobile application in the students’ learning performance has a little knowledge on the lesson, while the mean scores of the two groups after utilization shows that it has a significant effect on the learning performances. It shows that the developed mobiled application has a substantial effect on students learning performance in Physical education. Conclusion: The developed mobile application has a significant impact to the learning of the students in Physical education. This implies that the utilization of the technology in the teaching and learning process in physical education enhances the performance and ability of an individual.